HMGB1–Platelet Interactions: Mechanisms and Targeted Therapy Strategies - Fang, Xiyuan; Zhou, Xianghui; Zhou, Xin; Cheng, Zhipeng; Hu, Yu (Thrombosis and Haemostasis, 2025)
Platelets serve not only as crucial hemostatic components but also as pivotal regulators of inflammatory responses, capable of interacting with diverse cell types and secreting abundant extracellular factors. Accumulating evidence demonstrates that high mobility group box 1 (HMGB1), a DNA-binding protein and critical inflammatory mediator, plays multifaceted roles in disease progression, with platelets being one cellular source of circulating HMGB1. Under pathological conditions, platelets release HMGB1 into the extracellular matrix, establishing bidirectional communication between platelets and other immune cells. Moreover, HMGB1 reciprocally activates platelets through Toll-like receptors (TLRs) and receptor for advanced glycation end-products (RAGE), facilitating platelet activation and subsequent release of regulatory factors that drive inflammation-associated pathological thrombosis. In this review, we systematically characterize the HMGB1–platelet axis and elucidate its context-dependent roles in specific disease states. The mechanistic interplay between HMGB1 signaling and platelet pathophysiology is discussed, particularly its implications for disease progression. Furthermore, we critically evaluate therapeutic strategies targeting HMGB1 developed over the past decade, while proposing future directions for dual-target interventions that simultaneously modulate HMGB1 and platelet activity to combat inflammation-driven thrombotic disorders.
Keywords: HMGB1; platelet activation; proinflammatory; therapy